2017
DOI: 10.15666/aeer/1501_525540
|View full text |Cite
|
Sign up to set email alerts
|

Air-Drying Effect on Soil Reaction and Phosphorus Extractability From Upland-Lowland Tropical Soils as Related to Their Colloidal Stability

Abstract: Abstract. Although air-drying is a universally accepted practice for preserving soils before analyses, it can irreversibly affect certain soil processes and, hence, results of soil analyses. Reports about such effects on extractable/available phosphorus (P av ) are conflicting and are scanty for low-P av tropical soils. Moreover, little is known about its relative effects for well and poorly drained soils or about any underlying role of soil colloidal stability. In this study, soil samples from well-drained up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…That of available phosphorus was unexpected, considering the fact that the soil was only slightly acidic. This observation thus highlights the well-known low status of phosphorus availability in tropical soils (Owusu-Bennoah et al 1995;Obalum and Chibuike 2017).…”
Section: Resultssupporting
confidence: 59%
“…That of available phosphorus was unexpected, considering the fact that the soil was only slightly acidic. This observation thus highlights the well-known low status of phosphorus availability in tropical soils (Owusu-Bennoah et al 1995;Obalum and Chibuike 2017).…”
Section: Resultssupporting
confidence: 59%
“…For Sawah , soil pH was the only parameter that showed appreciable decline. Though this has been attributed to excessive leaching (Ali et al, ; Darmawan et al, ) and air drying effect on soil pH in lowland soils (Obalum & Chibuike, ), it should be noted that bunds demarcating Sawah basins serve as barriers against surface runoff and erosion known to be the major processes contributing to soil degradation in the study area. Such bunds also make for efficient management and use of water and nutrient resources, hence the 'slight' change in soil quality under Sawah .…”
Section: Resultsmentioning
confidence: 94%
“…Also, because the lowland Sawah soil was seasonally always puddled and submerged, greater dispersibility of clay would be expected under Sawah compared with TRF, for instance. The reductive effect of the routine preanalyses air drying on soil pH has been reported to increase with increase in water‐dispersible clay content of upland‐lowland soils (Obalum & Chibuike, ), hence the observation under Sawah .…”
Section: Resultsmentioning
confidence: 99%
“…The slope was larger than 1, illustrating that the air-drying process decreased extractable P from soils using the Olsen P method. Obalum and Chibuike [37] reported that the process of soil air-drying increased and decreased the available P in upland and lowland soils respectively, and attributed the reason to the release of mobilized P by Fe (III) oxyhydroxides via the redox reaction in soils [38,39]. Soinne et al [40] reported that drying changed P distribution in soil particles with different sizes.…”
Section: Resultsmentioning
confidence: 99%